Facial Attractiveness of Chinese College Students With Different Sexual Orientation and Sex Roles - Hou, Juan; Sui, Lumeng; Jiang, Xinxin; Han, Chengyang; Chen, Qiang (Frontiers in Human Neuroscience, 2019)
Facial attractiveness refers to a positive and joyful emotional experience induced by the face of a target person and the extent to which other people are driven to be close to their wishes. Since the 1970s, face attractiveness has gradually emerged in western psychological research, but most of the studies were confined to heterosexuals. More recently, some scholars have pointed out that sexual orientation may affect the judgment of facial attractiveness of individuals. Based on previous literature, this study proposed to explore the different facial attractiveness of individuals with different sexual orientation and sexual roles. Participants in this study were divided into two types (according to sexual orientation and sexual role) by the Sex Role Inventory for College Students (CSRI). Also, the eye-tracking technique was used to record the path of eye movements, where face images were manipulated by sexual dimorphism clues. The results showed that (1) compared to heterosexual men, homosexual men were significantly more likely to choose masculine faces as more attractive faces in paired faces; (2) male homosexuals are likely to have the feminization bias, and female homosexuals are likely to have the masculinization bias; (3) The masculine faces are more attractive than feminine faces to participants whose sex role in feminine type and androgynous type.